Ekonomické a etické aspekty korupce - Volejníková Jolana (Univerzita Pardubice, 1999)
Corruption hurt everyon. It deepens poverty. It distors social and economic development, it erodes the provision of essential public services amd it undermines democracy. Instead of fair competition based on price, quality and innovation, corruption leads to competitive bribery. This harms trade and deters new investment. What is corruption ? Why fight corruption ? How do you measure the degree of corruption ? Is Czech Republic the corrupt country ? This paper analysis the same questions.
Keywords: Ekonomika; transformace; Korupce; etika